Editorial Note - Suphannachart, Waleerat (Asian Journal of Applied Economics, 2023)
This Volume 30 (June 2023 issue) is the first issue that the Applied Economics Journal (AEJ) is publishing online only. There have also been other changes to our journal during the first half of 2023. First, we have welcomed three new editorial board members: Professor Peter Warr from the Australian National University, Australia, Professor Arief Anshory Yusuf from Padjadjaran University, Indonesia, and Professor Phouphet Kyophilavong from the National University of Laos, Lao PDR. Second, we said goodbye and have given great thanks to our retired board members, Professor David Bessler and Professor Paitoon Kraipornsak. We are grateful to the retiring editors for their longstanding contributions to our journal and look forward to working with the new team, whose members have long and rich experiences in guiding high-quality journals in Asia. Third, we are proud to be included in the AgEcon Search at Waite Library, Department of Applied Economics, University of Minnesota. All articles published with us can now be accessed via the AgEcon Search. Fourth, we are planning to both change our title to be in line with the new TCI’s ISSN criteria as well as to improve our focus and scope to be more distinctive while still maintaining our strength in publishing articles in the field of applied economics. We will keep our authors and audiences updated of this title change via an announcement on our website. Please rest assured that the journal title change will not affect our current and future submissions. The change will only improve our journal to meet international standards. In this June 2023 issue, there are eight articles presenting various empirical findings in applied economics. The first three articles deal with macro-aspect issues investigating linkages among financial development, economic growth, and macroeconomic stability as well as examining the connection between institutional quality and unemployment. The other five articles present micro-aspect issues in the context of the Thai economy, covering a wide range of topics from eliciting discount rates, investigating the market power of e-commerce platforms and mobile payment behaviors, consumer behavior in OTT services subscriptions for content programming, and classifying and investigating the dynamics of rural households’ livelihood strategies. These articles are summarized as shown in the PDF.